The Analysis To Determinants Affecting On Audit Opinion: Evidence From Indonesia - Lely Indriaty (Jurnal Akuntansi, 2024)
This research aims to analyze the determinants that have effects on Audit Opinion Statements by independent auditors, namely: Auditor Education, Professionalism and Auditor Switching. This research is categorized as quantitative research with data collection methods using questionnaires for 60 independent auditors who work in eight Public Accounting Firms in Jakarta, Indonesia. Data was processed using Smart PLS version 3.00 to prove the hypothesis. The quality indicators of the questionnaire have passed the validity and reliability tests. The t-test results reveal that Auditor Education, Professionalism, and Auditor Switching partially have a positive and significant effect on Audit Opinion. The effect of Professionalism on Audit Opinion shows the lowest positive influence between the effect of Auditor Education and Auditor Switching on Audit Opinion. The main findings of this research reveal the lack of contribution of auditor professionalism in providing Audit Opinion Statements.